(untitled) (Annals of Medical Research, 2023)
Aim: A ganglion cyst is the most common benign mass on the wrist. They are frequently seen on the dorsal aspect of the wrist. These lesions, which show symptoms such as pain and limitation of movement, can become restrictive in daily life activities. Surgical methods are accepted as the gold standard in treating this lesion, with a wide range of treatment options. In our study, two new surgical methods were described for the open resection of wrist dorsal ganglion cysts, which were not previously described in the literature. Three surgical methods were compared in open surgery for wrist dorsal ganglion cysts. Materials and Methods: Our study divided 180 patients with three different surgical methods into three groups. The functional results of the patients were evaluated with VAS and DASH scores at the 1st, 3rd, 6th, and 12th months. Comparisons were made in terms of developing complications and recurrence rates. Results: As a result of the evaluation, it was found that the functional outcomes, recurrence, and complication rates of all three surgical methods were similar. Conclusions: Considering that the results of 2 different surgical methods not described before are similar to those in the literature, the surgical techniques we described can be safely used in wrist dorsal ganglion cyst surgery.